Gamma-Irradiated Influenza A Virus Provides Adjuvant Activity to a Co-Administered Poorly Immunogenic SFV Vaccine in Mice - Babb, Rachelle; Chan, Jennifer; Khairat, Jasmine E.; Furuya, Yoichi; Alsharifi, Mohammed (Frontiers in Immunology, 2014)
Many currently available inactivated vaccines require 'adjuvants' to maximise the protective immune responses generated against the antigens of interest. Recent studies in mice with gamma-irradiated influenza A virus (γ-FLU) have shown its superior efficacy compared to other forms of inactivated FLU vaccines and its ability to induce both potent type-I interferon (IFN-I) responses and the IFN-I associated partial lymphocyte activation. Commonly, IFN-I responses induced by adjuvants, combined in vaccine preparations, have been shown to effectively enhance the immunogenicity of the antigens of interest. Therefore, we investigated the potential adjuvant activity of γ-FLU and the possible effect on antibody responses against co-administrated antigens, using gamma-irradiated Semliki Forest Virus (γ-SFV) as the experimental vaccine in mice. Our data show that co-vaccination with γ-FLU and γ-SFV resulted in enhanced SFV-specific antibody responses in terms of increased titres by 6 fold and greater neutralisation efficacy, when compared to vaccination with γ-SFV alone. This study provides promising evidence related to the possible use of γ-FLU as an adjuvant to poorly immunogenic vaccines without compromising the vaccine efficacy of γ-FLU.